Detection of Histoplasma Capsulatum by Nested-PCR in Clinical Specimens - María Teresa Colella; Sofía Mata; Claudia Hartung; Celina Pérez; Arantza Roselló; Carolina Olaizola; Carmen Fernández; Silvia Magaldi; Félix Toro (Kasmera, 2007)
Histoplasmosis is a systemic mycosis whose diagnosis is based on clinical, mycological and immunological criteria. Identification of its etiological agent in biological samples is difficult to perform. We evaluated a nested-PCR technique to identify Histoplasma capsulatum in clinical specimens (blood and bone marrow) and reference strains. Three different methods for DNA isolation were tested based on the reagents Guanidine thiocyanate, Benzoyl chloride and Triton X-100. Among these procedures, Guanidine thiocyanate-based method yielded by utmost good qualityDNAand was easy to perform when used with clinical specimens. However, a better recovery of DNA was accomplished with the Triton-X-100 method. Reference strains of Paracoccidioides brasiliensis, Candida glabrata, Cryptococcus neoformans and Coccidioides immitis (C posadasii) were tested to assess PCR assay specificity. The samples were amplified by nested-PCR and analyzed by 3% agarose gel electrophoresis. Each of the reference strains showed the same signal upon amplification with a DNA band of 210 bases pairs, as well as 5 blood samples and 2 bone marrow specimens, with high sensitivity (10 picograms of Histoplasma capsulatum DNA) and specificity (no cross reactivity with P. brasiliensis, C. glabrata, C. neoformans and C. immitis). This technique has proved to be useful as a diagnostic technique.